Developing a Solution for Hybrid Classroom: A Pilot Study From a Malaysian Private University - Ayub, Enna; Lim, Chee Leong; Yeo, Donny Chuan Hoe; Ismail, Siti Ramadhaniatun (Frontiers in Education, 2022)
The COVID-19 pandemic brought about an opportunity for higher education institutions (HEI) to explore modes of education delivery other than face-to-face (F2F) and remote learning via fully online mode. The HEIs faced challenges for “business to resume as usual” when not all students were able to return to campus due to being held back in their home state or countries due to different stages of lockdown at their locations. At Taylor's, a hybrid learning mode was thought of to be the solution that can cater both to students who are on-campus and those who are off-campus. A pilot project based on a very practical-oriented classroom from the School of Food Studies and Gastronomy (SFSG) and Taylor's Culinary Institute (TCI) was kick-started to ensure a seamless learning experience for the students. The “pandemic pedagogy” based on real-life needs can be an opportunity to scale up learning for borderless learning in the future. This study reports on the initial development process and challenges and the findings from the pilot studies using a design-based research (DBR) approach.